PDTM-04. REDEFINING THE CELLULAR ARCHITECTURE OF DIFFUSE MIDLINE GLIOMAS WITH H3 K27M MUTATIONS THROUGH LARGE-SCALE SINGLE-CELL ANALYSES. (6th November 2017) - Filbin, Mariella; Tirosh, Itay; Hovestadt, Volker; Haberler, Christine; Pelton, Kristine; Czech, Thomas; Goumnerova, Liliana; Bandopadhayay, Pratiti; Louis, David; Kieran, Mark; Slavc, Irene; Ligon, Keith; et al.
Abstract: While human tumors are shaped by the genetic evolution of cancer cells, evidence also suggests that they display superimposed hierarchies reminiscent of normal development. Yet, relating the genetic and hierarchical models of cancer organization has been limited by technical challenges. Here, studying H3 K27M-mutant diffuse midline gliomas we profiled thousands of single cells from fresh tumors by RNA-seq and reconstructed the genetic and epigenetic cellular architecture of tumors in patients. We identified a subset of cancer cells that are differentiated along specialized glial programs while a distinct subset expresses oligodendrocyte precursor expression programs. By identifying distinct genetic clones, we show that these cellular architectures evolve during the progression of the tumors, suggesting that developmental programs and genetic influences coordinately determine tumor architecture. These results provide unprecedented insight into the cellular composition of midline brain tumors at single-cell resolution and may help harmonize the cancer stem cell and the genetic models of cancer, with critical implications for disease management.